2020
DOI: 10.3389/fneur.2020.00835
|View full text |Cite
|
Sign up to set email alerts
|

Neurostimulation and Reach-to-Grasp Function Recovery Following Acquired Brain Injury: Insight From Pre-clinical Rodent Models and Human Applications

Abstract: Reach-to-grasp is an evolutionarily conserved motor function that is adversely impacted following stroke and traumatic brain injury (TBI). Non-invasive brain stimulation (NIBS) methods, such as transcranial magnetic stimulation and transcranial direct current stimulation, are promising tools that could enhance functional recovery of reach-to-grasp post-brain injury. Though the rodent literature provides a causal understanding of post-injury recovery mechanisms, it has had a limited impact on NIBS protocols in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 256 publications
(316 reference statements)
0
10
0
Order By: Relevance
“…Although kinematic analysis to predict functional recovery after stroke has been used in human research ( 56 ), photothrombosis models in NHPs have never applied kinematic analysis to examine upper limb motor function ( 36 38 ). We found that the kinematic aspects of motor impairment were similar across humans and marmosets, as evaluated by kinematic indices commonly used for evaluating human stroke recovery (i.e., initial movement direction errors and the number of speed maxima).…”
Section: Discussionmentioning
confidence: 99%
“…Although kinematic analysis to predict functional recovery after stroke has been used in human research ( 56 ), photothrombosis models in NHPs have never applied kinematic analysis to examine upper limb motor function ( 36 38 ). We found that the kinematic aspects of motor impairment were similar across humans and marmosets, as evaluated by kinematic indices commonly used for evaluating human stroke recovery (i.e., initial movement direction errors and the number of speed maxima).…”
Section: Discussionmentioning
confidence: 99%
“…( 5) Stimulation was delayed until 3 days after stroke, and therefore this intervention may be used in patients that are stabilizing post-stroke and/or missing the time window to receive tPA or thrombectomy. It is believed that most recovery from impairment in humans resulting from enhanced plasticity occurs in the first 1-3 months after stroke (25,77). The cortical plastic responses to stroke are particularly active within days or weeks after stroke in rodents (78)(79)(80).…”
Section: Discussionmentioning
confidence: 99%
“…This test was first performed as designed by Whishaw and our laboratory (22,23) and used as described in our previous work (18,20,21,24). It is well-established that the sensorimotor circuitry controlling motor control and related reaching and grasping of skilled reaching behavior is highly conserved in mammals (25). In brief, animals were placed in a transparent Plexiglas chamber (30 × 36 × 30 cm) with a rectangular opening (1.5 × 3 cm) in one wall.…”
Section: Skilled Forelimb Reaching Testmentioning
confidence: 99%
“…Another important part of the stimulation protocol is the timing of the treatment application after injury, which depends on the selected treatment modality, the severity of the trauma and the goal of the treatment [ 135 ]. The onset of stimulation in preclinical studies varies from immediately to several weeks after trauma [ 25 ].…”
Section: State-of-the-artmentioning
confidence: 99%